Study on the mechanical traits, failure mechanisms, energy responses, and influencing factors of columnar jointed basalts under direct and indirect tensile conditions - Liang, Dan; Yang, Haiqing; Ping, Zekang; Wang, Yongyi; Song, Kanglei; Chen, Chiwei; Li, Hao; Li, Xingyue; Peng, Lixin; Ju, Anhua (Frontiers in Earth Science, 2025)
In this study, by merging mesoscopic damage mechanics, the probabilistic strength principle, and continuum mechanics, the visuals of columnar jointed basalts (CJBs) featuring various joint arrangement patterns are converted into inhomogeneous numerical models utilizing the digital visual analysis based on the digital image correlation (DIC)-enhanced rock failure process analysis (RFPA). The strength–deformation traits, rupture features, and energy progression trends of CJBs subjected to direct tension and indirect tension (Brazilian splitting) are explored and compared. The acoustic emission (AE) energy buildup linked to the specimen’s peak stress is defined as the micro-crack energy index (MCEI), and the impact of multiple factors on the MCEI is analyzed. A factor sensitivity analysis is conducted. The study reveals that compared to the Brazilian splitting condition (BSC), under the direct tensile condition (DTC), the tensile strength (TS) and equivalent deformation modulus (EDM) of specimens in directions I and II (perpendicular to the column axis) are higher. In the direction parallel to the column axis, compared to the DTC, the TS of the specimens under the BSC is lower at the column tilt angle β = 0°–60° and higher at β = 75°–90°. Under the BSC, damage and fracture occur on the joints and columns within a localized area along the longitudinal centerline of the specimen. Considering diverse influencing factors and compared to the DTC, the MCEI for β = 30° specimens appears at a later stage and exhibits a lower magnitude under the BSC. When subjected to the DTC, the sensitivity of the MCEI to diverse factors ranks, in decreasing order, as follows: joint strength, the secondary joint set, joint constitutive behavior, meso-rock strength, and the rock homogeneity index. However, under the BSC, the sensitivity of the MCEI to joint constitutive behavior is higher than that to the secondary joint set. These findings can function as an academic foundation for understanding the sequence of emergence and magnitude differences of MCEIs in CJBs under tensile conditions, thus providing a scientific basis for rock mass engineering monitoring, reinforcement, and operational maintenance.